The Role of Physical Education towards First Year Sport Participation at the University of Johannesburg - Clinton Swanepoel; Roberto Lourenco; Kezia Appolis; Craig Harron (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The integration of the Physical Education as an outcome within the Life Orientation and Life Skills curriculum in South Africa has reduced instructional quality due to a lack of specialised educators. Within the school curriculum, it is uncertain if Physical Education plays a role in learners choosing to take part in school sport, and university sport. This lack of knowledge in understanding the importance of attitudes and perceptions toward Physical Education and school-based sports in the South African context requires further investigation, particularly regarding the impact that Physical Education has on university students' sports participation. The study entailed conducting semi-structured interviews with first-year University of Johannesburg sport students. The researchers obtained consent from athletes, conducted face-to-face semi-structured interviews, transcribed audio recordings, and employed thematic analysis using ATLAS.ti, revealing recurrent themes aligned with study goals.  The purpose of the study was to investigate the impact of Physical Education and school sport on sport participation among first year students taking part in sport at the University of Johannesburg.  The presence of well-trained Physical Education teachers, adequate facilities, equipment, and support systems positively correlates with increased participation in both school and university-level sports. This study underscores the pivotal influence of well-trained Physical Education educators, coupled with the provision of adequate facilities, equipment, and comprehensive support systems, in bolstering sport participation, encompassing both school and university contexts. This research highlights the paramount importance of these components in fostering active sports engagement among first-year students at the University of Johannesburg.